Clinical impact of serum survivin positivity and tissue expression of EBV-encoded RNA in diffuse large B-cell lymphoma patients treated with rituximab–CHOP - Hong, Jung Yong (Oncotarget, 2017)
Survivin is an inhibitor of apoptosis and is upregulated by Epstein–Barr virus (EBV) latent genes. Given the frequent association of EBV with lymphoid malignancies, survivin is expected to have prognostic value in diffuse large B-cell lymphoma (DLBCL). Thus, we measured the pretreatment serum level of survivin in DLBCL patients and analyzed its association with survival outcome and EBV status, as represented by EBV-encoded RNA (EBER) in DLBCL. Pretreatment serum survivin level was measured in patients registered in a prospective cohort study (n = 210), and serum survivin-positivity was defined as any detectable level of survivin. EBV status was determined using EBER in situ hybridization, and EBER-positivity was defined as 20% of examined cells showing nuclear positivity. Mean serum survivin level was higher in patients with relapsed or refractory disease than with responsive disease (59.89 pg/mL versus 17.34 pg/mL, P = 0.041). Serum survivin-positive patients had worse overall and progression-free survival (P = 0.023 and 0.022, respectively). Serum survivin positivity was associated with unfavorable characteristics including stage. In patients with non-germinal center B-cell type DLBCL, serum survivin-positive patients also had significantly worse survival than serum survivin-negative patients (P < 0.001). EBER-positivity was found in 6.7% (14/210) of patients, and EBER-positive patients had worse survival (P < 0.05). Patients having concomitant positivity for serum survivin and EBER expression (2.8%, 6/210) showed extremely poor prognosis. In the present era of rituximab in DLBCL, DLBCL with serum survivin positivity showed adverse clinical features and followed worse clinical course, especially in non-GCB subtype DLBCL. EBER-positivity was still associated with worse outcomes in DLBCL.